Compartment-based reconstruction of acquisition-weighted 31P cardiac MRSI reduces sensitivity to cardiac motion and scan planning - Tyler, Andrew; Hundertmark, Moritz J.; Miller, Jack J.; Rider, Oliver; Tyler, Damian J.; Valkovič, Ladislav (Frontiers in Physiology, 2024)
Motivation: 31 P magnetic resonance spectroscopic imaging ( 31 P MRSI) is a powerful technique for investigating the metabolic effect of treatments for heart failure in vivo, allowing their mechanism of action in patient cohorts to be better understood. Unfortunately cardiac 31 P MRSI is fundamentally limited by low SNR, which leads to compromises in acquisition, such as no cardiac or respiratory gating or low spatial resolution, in order to achieve reasonable scan times. SLAM reconstruction, may be able to address these challenges, and therefore improve repeatability, by incorporating a segmented localizer into the reconstruction.Methods: Six healthy volunteers were scanned twice in a test-retest procedure to allow quantification of repeatability. Each scan consisted of anatomical localizers and two acquisition weighted (AW) 31 P MRSI acquisitions, which were acquired with and without cardiac gating. Five patients with heart failure with preserved ejection fraction were then scanned with the same 31 P MRSI sequence without cardiac gating. All 31 P MRSI datasets were reconstructed with both a conventional Fourier transform (FT) based reconstruction, and the SLAM reconstruction, which were compared statistically. The effect of shifting the 31 P MRSI acquisition field of view was also investigated.In the healthy volunteer cohort, the spectral fit of the SLAM reconstructions had significantly improved Cramer Rao lower bounds (CRLB) compared to the FT based reconstruction of non-cardiac gated data, as well as improved coefficients of variability and repeatability. The SLAM reconstruction found a significant difference in PCr/ATP ratio between 1the healthy volunteer and patient cohort, which the FT based reconstruction did not. Furthermore the SLAM reconstruction was less influenced by the placement of the field of view (FOV) of the 31 P MRSI acquisition in post-hoc analysis.The experimental benefits of the SLAM reconstruction for AW data were demonstrated by the improvements in fit confidence and repeatability seen in the healthy volunteer cohort and post-hoc FOV analysis. The benefit, to clinical studies, of SLAM reconstruction of AW data was then illustrated by the patient cohort, which suggested improved sensitivity to clinically significant changes in PCr/ATP ratio.